Second-order analysis and design of angle trusses Part I: Elastic analysis and design - Chan, S.L.; Cho, S.H. (Engineering structures, 2008)
Angle members are widely used in light-weight steel skeletons and they are commonly subject to high axial force with eccentricity. Different design codes recommend varied load resistances and second-order analysis widely used in design of steel frames of doubly symmetrical sections is seldom reported. This paper fills the gap by proposing a practical second-order analysis and design method for trusses composed of angles sections. Realistic modeling of semi-rigid connections associated with one- and two-bolt end connections with flexible gusset plate and member imperfections such as initial curvatures and residual stresses is made. Load eccentricity is also simulated. The proposed method can be readily applied to reliable, robust, efficient and effective design of angle trusses and frames without the uncertain assumption of effective length.